Kilometer-scale trends, variability, and extremes of the Adriatic far-future climate (RCP 8.5, 2070−2100) - Tojčić, Iva; Denamiel, Cléa; Vilibić, Ivica (Frontiers in Marine Science, 2024)
Due to orography-driven dynamics at a (sub-)kilometer scale (e.g., the bora wind) and a complex ocean bathymetry that includes numerous channels, depressions and ridges, the atmosphere-ocean dynamics within the semi-enclosed Adriatic region is not well reproduced by the available regional climate models. The Adriatic Sea and Coast (AdriSC) kilometer-scale atmosphere-ocean model was thus specifically developed to accurately assess the Adriatic climate hazards under both historical (1987-2017) and far-future (2070-2100) conditions. In this study, we analyze the impact of climate change on the projected Adriatic trends, variability and extreme events. In the atmosphere, our results mostly follow the already published literature: strong land-sea contrasts, increased droughts and extreme rainfall events, and decreased wind speeds in the coastal areas. In the ocean, strong and constant rise in surface and intermediate temperatures is associated with salinity decrease, except in surface during summer when salinity rises in the coastal areas. At the bottom and for the ocean circulation, our results exhibit strong contrasts. In the coastal areas, bottom temperature rises, and bottom salinity decreases at the same rate than in surface while changes in current speed are negligible. In the deepest part of the Adriatic, negative bottom temperature trends result in a rise 2.5°C slower than in surface while bottom salinity increases. Further, ocean currents accelerate in the surface and intermediate layers but decelerate at the bottom. These ocean results suggest a reduction of the dense water formation in the northern Adriatic, an intensification and shrinking of the southern Adriatic cyclonic gyre, and a strengthening of the vertical stratification in the deepest part of the Adriatic probably linked to changes in the Adriatic-Ionian water mass exchanges. Given the potential impact of these changes on the Adriatic coastal communities and marine life, this study highlights the need to increase the ongoing kilometer-scale modelling efforts in the Adriatic region with the aim to implement policies and adaptation plans better tailored to the local climate changes projected in this specific region.